Peningkatan Hasil Belajar Siswa Kelas V SD Negeri Tanamodindi Pada Tema 1 Organ Gerak Hewan dan Manusia Melalui Model Pembelajaran Kooperatif Tipe STAD Berbantuan Media Animasi Powtoon - Hidayat; Ratman; Rizal; Surahman (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2023)
This study aims to improve the learning outcomes of Grade V students at SD Negeri Tanamodindi through the use of Powtoon animation media in science lessons. The action research follows the Hopkins model, which includes planning, action implementation, observation, and reflection. The results of the study showed that teacher activity in the first cycle reached 70.83%, and in the second cycle, it increased to 85.42%, with a 14.59% improvement in teacher activity. For student activity, the percentage was 65.91% in the first cycle and increased to 84.09% in the second cycle, resulting in an 18.18% improvement in student activity. This indicates that in the first cycle, both teacher and student activities fell into the